Thomas Aquinas on the passions : a study of Summa theologiae, 1a2ae 22-48 - Miner, Robert C., 1970- (Cambridge Univ. Press, 2009)
The Summa Theologiae is Thomas Aquinas' undisputed masterwork, and it includes his thoughts on the elemental forces in human life. Feelings such as love, hatred, pleasure, pain, hope and despair were described by Aquinas as 'passions', representing the different ways in which happiness could be affected. But what causes the passions? What impact do they have on the person who suffers them? Can they be shaped and reshaped in order to better promote human flourishing? The aim of this book is to provide a better understanding of Aquinas' account of the passions. It identifies the Aristotelian influences that lie at the heart of the Summa Theologiae, and it enters into a dialogue with contemporary thinking about the nature of emotion. The study argues that Aquinas' work is still important today, and shows why for Aquinas both the understanding and attainment of happiness requires prolonged reflection on the passions.